A Secular Age: an exercise in breach-mending - Flanagan, Kieran (New blackfriars, 2010)
This article considers three aspects of Taylor's A Secular Age: the issue of the status and authority of theological insights derived from sociological analyses; the irresolvable ambiguities of secularity, where it marks the disappearance of religion but inadvertently affirms its persistence; and the properties of nostalgia and memory that unexpectedly shape post-secularity and the forms of enchantment it seeks.